Ontario feed-in-tariffs: System planning implications and impacts on social welfare - Mehrdad Pirnia; Jatin Nathwani; David Fuller (The Electricity Journal, 2011)
An analysis of the policy implications of Ontario's FITs on overall societal welfare suggests that, if unbounded, existing FIT tariffs would have a large negative impact on consumer welfare, with an overall net loss on total social welfare. Negative impacts could be minimized by controlling the quantities.